ナンキョク タイキ ノ スイジョウキ ト コウスイチュウ ノ アンテイドウイタイ ソセイ - Schwarz, Gunter; Ohm, Klaus; 山内, 恭; ヤマノウチ, タカシ; 古川, 晶雄; フルカワ, テルオ; Kowski, Peter; Gernandt, Hartwig; Yamanouchi, Takashi; Furukawa, Teruo (1996)
P(論文) 日本南極観測隊の昭和基地とドームふじ観測拠点で得られた大気の水蒸気と降水中の安定同位体の分析を行った。主なサンプリング期間は1995年1月である。この短い期間にもかかわらず, 重水素と^<18>Oの標準海水試料(SMOW)との偏差である同位体比には大きな幅が出た。昭和基地における降水中のδ^<18>Oと開水面までの距離との間には有意な関係が見いだされた。極端な値の同位体比は, どちらの基地においても, 低緯度側から空気が運ばれてくる場合に見られた。今回の結果は, 昭和基地とドームふじ観測拠点における, 1997年1月までの2年間の観測の第1報である。 First results of stable isotope analyses are presented which were obtained by sampling of air moisture and precipitation at the Japanese Antarctic Stations Syowa and Dome Fuji. The main sampling period was during January 1995. Even within this short period their isotopic composition, expressed in delta values of deuterium and ^<18>O relative to the standard mean ocean water (SMOW), are scattered over a wide range of magnitudes. A weak, but significant, quantitative relationship between δ^<18>O of precipitation at Syowa and the distance to the open sea was found. Extreme high isotopic delta values appear at both stations when air is transported from lower latitudes to the Antarctic continent. These preliminary results were obtained from observations in January 1995. They will be continued at these stations for about two years by January 1997. departmental bulletin paper